Analysis of the statute and the first year of the activities of Lviv Society of Halician Physicians («Towаrzystwo lekarzów Galicyjskich»). - I. R. Berest; R. Ya. Berest; M. S. Pasichnyk; H. M. Savchuk; M. A. Oliynyk (Medičnì Perspektivi)
Based on the principle of historicism, system analysis, structural functionalism, dialectics and synergetics, the paper analyzes the charter and activity the of the Lviv Society of Halician Physicians, the first trade union organization in the medical sphere. Contemporary codition as well as development of historiography of the issue including the history of the medical and trade union movement, the names of the Society founders is shown. The crucial problem among physicians of the second half of the nineteenth century which was in line with the problems of all population segments is proved. This organization played a prominent role in the development of medicine in Halychyna. The activity of the Society was regulated by the charter. Each member, when joining the Society, assumed the obligation to comply with all the provisions of the charter and had to care for its growth and the glory of the organization. Acting members had to be present at scientific meetings and provide observations on the status of the medical case. That is, to provide statistics on the diseases and patients they have been treated, as well as to share the experience gained in practice. The purpose of the organization and its activities were primarily socio-economic and cultural-educational ones. Under its control, the Society kept a record of the movement of patients in Lviv hospitals (kept statistics of all cured patients), analyzed new methods in the treatment of fever, various pathologies and other issues. The members of the Society promised to meet every first Saturday of the month to participate in scientific meetings. They discussed major events in the life of the organization, read correspondence and planned work for the next month. Once a year, in December, the Society of Galician physicions held an annual meeting, which provided a full annual financial report, discussed the issues of new members and those who left the organization, announced the names of new honorary and advisory members.